Analisis Tuturan Ritual Tawar Pengobatan di Desa Penyinggahan Kabupaten Kutai Barat Kalimantan Timur: Ditinjau Dari Bentuk Dan Fungsi Mantra - Dawati, Sri; Ahmad, M. Rusydi; Rijal, Syamsul (Adjektiva: Educational Languages and Literature Studies, 2019)
The problems studied in this study are (a) How the form of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West; (b) How the function of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West; (c) How the meaning of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West. The aim of the research These are (a) To describe the form of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West; (b) To describe the function the ritual of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West; (c) To describe the meaning of speech of treatment bid ritual in Penyinggahan Village, Kutai Regency West. Methods used in research This is method analsys using observation techniques, structured interviews, note, record and listen. Research results obtained from data analysis that has been done by the author, the results of the research are (i) Mantra consists of several series of rhyming words; (ii) is verbal, magic or magical; (iii) asopheric (a special language between the speaker and the interlocutor); (iv) there are words that are less commonly used in everyday life. Function the bargaining spell of the treatment of the Kutai tribe based on the results of its function analysis, namely (i) The function of the mantra as a social controller; (ii) The spell functions as tolerance; (iii) The function of the mantra as a means to pray.